ANALYSIS OF THE FACTORS AFFECTING THE COST OF SHIP REPAIRS IN THE ISLAND OF JAVA AND KALIMANTAN - Arif, Mohammad Sholikhan; Hutabarat , Darryl Oliver Benedict; Pribadi, Triwilaswandio Wuruk; Wahidi, Sufian Imam; Supomo, Heri; Pribadi, Sri Rejeki Wahyu (Journal of Marine-Earth Science and Technology, 2022)
The national shipbuilding industry is primarily responsible for maintaining and repairing ships at ship repair facilities to ensure their seaworthiness. Each shipyard offers variable pricing for ship repair, mainly if the work is performed on different islands, in Java and outside of Java. By understanding the differences in ship repair costs between shipyards in Java and those outside of Java and the factors that influence these discrepancies, a ship owner can choose a repair shipyard for docking his vessel. Ship repair data were collected from shipyards in Java and Kalimantan, with data collection and direct surveys conducted at three Industries which are located in the island of Java, and three industries in Kalimantan Island, it is processed to determine the difference between the average cost of ship repairs at shipyards in Java Island and Kalimantan Island, revealing that the cost of repairing ships at shipyards in Java Island is higher than the cost of repairs at shipyards on Kalimantan Island. However, there are also increased costs associated with ship maintenance activities in shipyards in the island of Kalimantan. After processing the difference data, the identification of the factors that cause the difference in repair costs forms, and the identification results indicate that the difference in ship repair costs at the shipyards in Java and Kalimantan is influenced by differences in service costs, productivity figures, geographical location of the shipyards, supply chains. materials, as well as the completeness, quality, and capacity of repair support facilities at the shipyards.